Usher syndrome proteins ADGRV1 (USH2C) and CIB2 (USH1J) interact and share a common interactome containing TRiC/CCT-BBS chaperonins - Linnert, Joshua; Knapp, Barbara; Güler, Baran E.; Boldt, Karsten; Ueffing, Marius; Wolfrum, Uwe (Frontiers in Cell and Developmental Biology, 2023)
The human Usher syndrome (USH) is the most common form of a sensory hereditary ciliopathy characterized by progressive vision and hearing loss. Mutations in the genes ADGRV1 and CIB2 have been associated with two distinct sub-types of USH, namely, USH2C and USH1J. The proteins encoded by the two genes belong to very distinct protein families: the adhesion G protein-coupled receptor ADGRV1 also known as the very large G protein-coupled receptor 1 (VLGR1) and the Ca2+- and integrin-binding protein 2 (CIB2), respectively. In the absence of tangible knowledge of the molecular function of ADGRV1 and CIB2, pathomechanisms underlying USH2C and USH1J are still unknown. Here, we aimed to enlighten the cellular functions of CIB2 and ADGRV1 by the identification of interacting proteins, a knowledge that is commonly indicative of cellular functions. Applying affinity proteomics by tandem affinity purification in combination with mass spectrometry, we identified novel potential binding partners of the CIB2 protein and compared these with the data set we previously obtained for ADGRV1. Surprisingly, the interactomes of both USH proteins showed a high degree of overlap indicating their integration in common networks, cellular pathways and functional modules which we confirmed by GO term analysis. Validation of protein interactions revealed that ADGRV1 and CIB2 mutually interact. In addition, we showed that the USH proteins also interact with the TRiC/CCT chaperonin complex and the Bardet Biedl syndrome (BBS) chaperonin-like proteins. Immunohistochemistry on retinal sections demonstrated the co-localization of the interacting partners at the photoreceptor cilia, supporting the role of USH proteins ADGRV1 and CIB2 in primary cilia function. The interconnection of protein networks involved in the pathogenesis of both syndromic retinal dystrophies BBS and USH suggest shared pathomechanisms for both syndromes on the molecular level.